Ilustração botânica de um Brasil desconhecido - Rosa Maria Alves Pereira (2011)
In order to give visibility to the collection of the Philosophical Journey from the naturalist Alexandre Rodrigues Ferreira, and to demonstrate the real importance of his great legacy in the realm of botany, a science awarded with most of his collections in Brazil, this study explores the theoretical and practical aspects of the Scientific Illustration, and adds historical value to the work of the greatest Brazilian naturalist of all times. In theoretical research, the crucial importance of Scientific Illustration to the scientific revolution fomented in the eighteenth century by the Portuguese empire was detached. The Portuguese exploited the natural wealth of their colonies in voyages of political and economic interests. These expeditions to the Brazilian Amazon and Cerrado from 1783 to 1792 revealed the accuracy of shapes and colors by the hands of the designers José Joaquim Freire and Joaquim José Codina, as well as the richness of the soil, fauna, flora, people and culture. The main historical organizations that permitted the reconstruction of the Philosophical Journey were the Botanical Gardens with their living plants, and the Museums of Natural Sciences with their herbaria and collections of exsiccates. These organizations were also fundamental to the discovering of the fate of the valuable scientific collection which passed by the destructive political events and natural disasters that marked the era, and were determinant for the knowledge on the loss and misdelivering of much of the memories and collections sent to Lisbon. The wrong information about the death of the designer José Joaquim Codina during the expedition route was proved to be false due to the analyses of a document proving his return to Lisbon with a fellow designer, two Indians and the scientist Alexandre Rodrigues Ferreira. Also, the magnitude of the beauty and usefulness of Botanical Illustration enabled a consistent understanding of both the elements and factors that dictated and structured the process of its creation, as well as the potential for teaching and learning inserted in its scientific content. In field research, the methodology centered on the observation of dry preserved 200 years-old specimens under a stereomicroscope, the choice of watercolor technique, and the preliminary definition of the details of composition. Details such as the evidence of the leaf scars on the stem with their corresponding cracks, presence or absence of bark, cracks and kinks, identification of textures and supporting structures, together with measurements, such as the length of the specimen including the petiole, and the maximum width of the leaf blade were observed. This detailed observation permitted the creation and development of a specific technique for reconstruction drawing of herborized plants with the appearance of living plants, which enabled the creation of the catalog with 16 watercolors entitled "Unknown Brazil", made by this author.